The effect of government size on globalization in selected countries with a dynamic panel approach - JAFAR yahyavi dizaj; yosef mohamadzade (پژوهش‌های برنامه و توسعه)
AbstractAppropriate share of the economic markets, political interaction, social and cultural activities need international contact and properties almost similar conditions in the domestic environment. The presence of government in national markets one of the most important factors that indoor exposure especially with global competition undermines the national economy. This study aimed to investigate the effect of government size on globalization in 95 selected countries around the world between 1985-2014 using dynamic panel model (GMM) was performed. In this paper, multiple indicators for example globalization index KOF, attract foreign direct investment and share of export of domestic production has been studied. The results show that significant negative correlation between government size and globalization of society. It can be said that the widespread presence of government can interact successfully in a global society and international markets to weaken the economy. As well as the effects of other variables in the models suggest that human development, control of corruption, expenditure on research and development and increase domestic production have positive impact but inflation and high rates of tariffs have negative impact on economic success in attracting international investment and exports there.